Penguatan Kompetensi Guru TK Dalam Pengajaran Bahasa Inggris Melalui Pendekatan Interaktif dan Menyenangkan - Dyah Roma Wati; Dwi Cahyono; Shinta Aprilia (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2026)
Teaching English to young learners requires teachers to use methods that align with children’s developmental stages. However, many Aisyiyah kindergarten teachers affiliated with IGABA in Karanganyar District lack an English education background and continue to use conventional teaching approaches. This community service program aimed to enhance teachers’ competence in delivering interactive and engaging English instruction through the use of Total Physical Response (TPR) and songs. The training, held at TK Aisyiyah Bibis, involved 15 teachers from various Aisyiyah kindergartens in Karanganyar District. The program consisted of an initial survey and interviews, coordination, material preparation, concept presentation, TPR and song simulations, group discussions, and evaluation through Q&A sessions and direct observation. The results showed that participants gained new insights into English instruction for young learners, especially regarding the use of commands and physical movement in TPR, as well as songs for teaching vocabulary, pronunciation, and simple sentence patterns. The participants’ enthusiasm, active questioning, and constructive feedback reflected a positive response to the introduced methods. Regular follow-up training is recommended, particularly to further strengthen teachers’ mastery of daily expressions and their classroom application.